PEMBASIINDO (PEMBELAJARAN BAHASA ISYARAT INDONESIA) BESBASIS ANDROID DI SEKOLAH LUAR BIASA NEGERI 02 MAKASSAR - Umar, Andi Achmad Zufadly; Satma, Satma; Mukarramah, Rifqatul; Agung, Riski Dewa; Amir, Nur Hikmah; Indra, Dolly; Hayati, Lilis Nur (Jurnal Balireso: Jurnal Pengabdian pada Masyarakat, 2019)
Many inhabitants of Indonesia, including individuals who have physical characteristics, thecharacters are different traits supplied by heredity and the formation of characteristics related tothe physical environment and social environment. Based on these factors, humans are classified asnormal people and those with special needs such as deaf. At Sekolah Luar Biasa Negeri 02Makassar the sign language learning process still considered less effective because of the limitedteaching team. In the PKM-M activities, it aims to introduce the features that provide in AndroidbasedPEMBASIINDO consisting of video tutorials. The benefit of this activity is the teachingteam can carry out an effective learning process and the program can be useful as a learning mediathat can be used by the deaf and the general society. The Implementation method of these activitiescarried out at SLBN starts from observation, design activities, coordination with partner related tothe activities, socialization, and training PEMBASIINDO application. The results of theseactivities are related to increasing knowledge about Indonesian sign language by PEMBASIINDOapplication media, helping teachers to the learning process and students with hearing impairmentto communicating with their friends and the environment related to support the learning process.